(untitled) (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
This paper tries to show the posible relationship between the iberian words arsboiltiĚ and etem²iltiĚ, in a lead found in the Camp de Morvedre, and the place-names Arse (Sagunto) and Edeta (Cerro de Sant Miquel de Llíria), respectively.